2020
DOI: 10.1177/0748233720915109
|View full text |Cite
|
Sign up to set email alerts
|

Physiological status and functional anatomy of zebra fish (Danio rerio) exposed to various levels of Ga3+

Abstract: Gallium (Ga) is one of the intermetallic elements that has been used in cancer treatment for a long time. However, Ga compounds are increasingly being used to make high-speed semiconductors and photoelectric devices. The current work investigated physiological and pathological changes in zebra fish ( Danio rerio) exposed to various Ga3+ levels (0.55, 1.5, and 3.85 mg/L) over a 14-day test period. Decreases in oxygen consumption were significant ( p < 0.05) for groups exposed to 3.85 Ga3+ mg/L; this was asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Richard et al (2016) showed in their study that cement factory workers in Calabar, Nigeria, and the residents of the factory vicinity presented with derangements in the activity of LDH, AST, and ALT because of long-term exposure to the dust from the factory. LDH is a cytosolic enzyme the activity of which when found to be increased in the blood is suggestive of a leakage from the cell due to damage (Chang et al, 2020). LDH activity may also be used as a measure of stress level in snails (Abdel-Halim et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Richard et al (2016) showed in their study that cement factory workers in Calabar, Nigeria, and the residents of the factory vicinity presented with derangements in the activity of LDH, AST, and ALT because of long-term exposure to the dust from the factory. LDH is a cytosolic enzyme the activity of which when found to be increased in the blood is suggestive of a leakage from the cell due to damage (Chang et al, 2020). LDH activity may also be used as a measure of stress level in snails (Abdel-Halim et al, 2013).…”
Section: Discussionmentioning
confidence: 99%